OTOMATISASI ALAT PENGEPAKAN PERMEN SKALA HOME INDUSTRI BERBASIS MIKROKONTROLER ATMEGA 8535 - Arfianto, Dony Hardika; Subali, Subali (Gema Teknologi, 2012)
Dony Hardika Arfianto, Subali, in paper candy automation packing at home industry use ATMEGA 8535 microcontroller explain that in this modernization era, almost all activity uses of automation, both in the industrial middle, upper and home industry. If the process of candy packing can be automated it will be very advantageous for industrial-scale home industry. This candy packaging automation systems using a microcontroller ATmega 8535. The tool consists of a sensor LDR as sensor packaging, the heater as a tool for plastics pressing, conveyor as a driver and microcontroller ATmega 8535 as the main controller. Microcontroller ATmega8535 is one of the artificial Atmel microcontroller that has many uses. Price microcontroller is relatively cheap nowadays, if viewed from its facilities. Keywords: packing, LDR sensor, heater, microcontroller ATmega8535